The Predictive Power of Comprehensive Income of Listed Companies - Sajnóg, Artur Robert (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The main subject of theoretical‑empirical study presented in this paper is the estimate of the information significance of comprehensive income, primarily associated with the predictive power of this financial category. Realization of the fundamental objective of this paper was centered around the main research hypothesis, stating that the comprehensive income, as opposed to the traditional net income, has a stronger predictive power, because the predictive power of comprehensive income is associated with shaping the future financial results of company. The research comprised joint‑stock companies listed on the Warsaw Stock Exchange and included in WIG30 Index (qualified on 1.02.2016). Empirical data for the study was obtained from the quarterly financial statements (the period from 2009 to 2015).